2004
DOI: 10.1111/j.1467-839x.2004.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

‘The double identity’ of Taiwanese Chinese: A dilemma of politics and culture rooted in history

Abstract: The ‘double identity’ of Taiwanese as both Chinese and Taiwanese identity was measured among both general and student samples using categorical and continuous measures. As predicted, Mingnan (native province) Taiwanese were higher in Taiwanese identity whereas outside‐province Taiwanese were higher in Chinese identity. Both groups shared similar representations of the history of Taiwan, but evaluations of leaders followed patterns of in‐group favoritism. These representations of history were used to predict an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 23 publications
3
81
0
2
Order By: Relevance
“…But around election time, there are serious differences of opinion between the two groups about the future of the relationship with mainland China. Huang et al (2004) found that in the 2000 election, the historical evaluation of Chiang Kai-shek was a significant predictor of the vote for President between a native province and outside province candidate, even after controlling for demographic group and social identity. This shows how history is still influential for political decisions today.…”
Section: Social Representations Of History: From Hegemonic To Emancipmentioning
confidence: 99%
See 2 more Smart Citations
“…But around election time, there are serious differences of opinion between the two groups about the future of the relationship with mainland China. Huang et al (2004) found that in the 2000 election, the historical evaluation of Chiang Kai-shek was a significant predictor of the vote for President between a native province and outside province candidate, even after controlling for demographic group and social identity. This shows how history is still influential for political decisions today.…”
Section: Social Representations Of History: From Hegemonic To Emancipmentioning
confidence: 99%
“…The current situation in Taiwan is illustrative of how problems of the past can be connected to current political situations (Huang et al, 2004). Traditionally, Taiwan was a part of China, but Japan took over for about 50 years prior to World War II.…”
Section: Social Representations Of History: From Hegemonic To Emancipmentioning
confidence: 99%
See 1 more Smart Citation
“…A central element in most forms of nationalism is to assert the immortality of the group through time, establishing its origins in such as way as to justify its continued existence and rights and obligations today (Smith, 1998). Hence, psychologists have begun to examine how people use history to understand why the world is the way that it is, and how tradition and past experience can be used to justify political agendas (e.g., Huang, Liu, & Chang, 2004;Liu & Atsumi, 2008;Liu, Lawrence, Ward, & Abraham, 2002;Liu, Wilson, McClure, & Higgins, 1999;Pennebaker et al, 1997;Reicher & Hopkins, 2001;Sen & Wagner, 2005).…”
Section: Abstract: Group Processes; Intergroup Relations/prejudice; Nmentioning
confidence: 99%
“…Aside from capturing the ambivalence toward globalization that people in developing countries often experience, the good old days and better tomorrow effects are important for predicting popular support for social and economic changes in the society. People's historical representations and future imaginations of their country are important drivers of their reactions to the social, economic and political reforms in the country (Huang, 2007;Huang, Liu, & Chang, 2004;Liu & Hilton, 2005). Individuals with more positive future imaginations of their country (those who believe in a better tomorrow) are more likely to embrace progressive reforms and engage in the country's modernization effort, whereas those with strong nostalgic indulgence in the country's past tend to resist reforms that would cause further erosions of the country's core values.…”
Section: Introductionmentioning
confidence: 99%